Causes of low productivity of cocoa in Ghana: Farmers' perspectives and insights from research and the socio-political establishment - Dormon, E.N.A.; Van Huis, A.; Leeuwis, C.; Obeng-Ofori, D.; Sakyi-Dawson, O. (NJAS - Wageningen Journal of Life Sciences, 2004)
Ghana is a major producer of cocoa in the world and relies heavily on the crop for foreign exchange revenue. However, production declined since the mid-1960s, reaching its lowest level in 1983, Although production has increased consistently since the mid-1980s, it still is less than the level attained in the mid-1960s. The decline is partly a result of decreasing areas under cultivation. Another problem in cocoa production in Ghana is low yields per ha, which is attributed to the incidence of pests and diseases, a low producer price, and non-adoption of research recommendations. Based on the idea that current research and extension messages might insufficiently address farmers' actual problems and context, a diagnostic study was carried out to better understand farmers' views on the problems of cocoa production. The study was conducted in three villages in the Suhum-Kraboa-Coalter District, Eastern Region, Ghana. An action research approach was followed to gather and analyse qualitative data with the objective of stimulating collective action in subsequent research activities with the farmers. Low productivity was identified as the main problem and the causes were classified into biological and socio-economic factors. The biological factors include the incidence of pests and diseases, most of which have received extensive research attention in Ghana, and of epiphytes, which have been neglected. The socio-economic causes were indirect and include the low producer price and the lack of amenities like electricity, which leads to migration, with as a result labour shortages and high labour costs. From the study it can be concluded that the biological and socio-economic causes of low productivity are inter-related in such a manner that tackling them separately will not overcome the problem unless the socio-technical nature of the causes are recognized and tackled in a holistic way. In this context, current interventions by research and extension seem to ignore important aspects of the problematic situation. Although the study shows the relevance of using a diagnostic approach, it is argued that outcomes may be affected by various contextual factors, including stakeholder selection and the relationship between the researcher and the participants. Hence, the outcomes of a diagnostic study should be approached with care.
Keywords: Diagnostic study; Participatory action research